Regional Constraints on Soft Law Legitimacy: Some Australian Geopolitical Perspectives. - Herr, Dr. Richard (2011)
Dr. Richard Herr, School of Government, University of Tasmania, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.